Intravascular Fasciitis of the Jugular Vein Mimicking Thrombosis and Sarcoma: A Case Report - Chen, Guo Xin; Chen, Chu Wen; Wen, Xiao Rong; Huang, Bin (Frontiers in Surgery, 2021)
Background: Intravascular fasciitis is an uncommon variant of nodular fasciitis, which is a reactive proliferative lesion of myofibroblasts. There have been rare reports of that intravascular fasciitis has invaded the jugular vein, as seen in this case. Case presentation: A female in her 41-year-old presented with right neck dull pain for 20 days. Grossly, the mass was pink hyaline, oval, and well-demarcated, measuring approximately 5 mm in diameter. Microscopically, the mass was composed of spindle cells arranged intersecting fascicles. Immunohistochemical stains showed the spindle cells were positive for smooth muscle actin and negative for S-100, Desmin, MyoD1 and elastin stains. The nuclei of the spindle cells were relatively uniform and mitotic activity was observed. The overall morphological and immunohistochemical features are consistent with intravascular fasciitis. Conclusion: By reporting this rare case, we would like to raise the awareness of this non-neoplastic lesion to avoid misdiagnosing it as a sarcoma or thrombosis. Previously reported similar cases were also reviewed and compared with this case.